Proceedings of the Ocean Drilling Program 1993
DOI: 10.2973/odp.proc.sr.130.014.1993
|View full text |Cite
|
Sign up to set email alerts
|

Cenozoic Stratigraphy and Paleoceanography of Biserial Planktonic Foraminifers, Ontong Java Plateau

Abstract: The Ontong Java Plateau in the western equatorial Pacific contains a deposition record of biserial planktonic foraminifers concentrated in the Paleogene, in which frequencies up to 67% of the planktonic foraminifers are reported, and in the late Neogene, in which a maximum frequency of 48% is reported. Biserial planktonic foraminifers are rare or absent in the latest Oligocene and early Miocene, an interval characterized by warm bottom water and low temperature gradients. These conditions supported a surface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The presence of Streptochilus latus in sample Mf11682 and the Hart Mine Wash section indicates a late Miocene age between 8.1 and 5.3 Ma (Resig, 1989(Resig, , 1993. This age is confi rmed by the occurrence of Streptochilus cf.…”
Section: Age and Correlationmentioning
confidence: 77%
See 1 more Smart Citation
“…The presence of Streptochilus latus in sample Mf11682 and the Hart Mine Wash section indicates a late Miocene age between 8.1 and 5.3 Ma (Resig, 1989(Resig, , 1993. This age is confi rmed by the occurrence of Streptochilus cf.…”
Section: Age and Correlationmentioning
confidence: 77%
“…A complete and well-preserved fossil record in the western Pacifi c and Indian Ocean has allowed recognition of the biostratigraphic relevance of this genus (Resig, 1989(Resig, , 1993.…”
Section: Paleontologymentioning
confidence: 99%
“…Therefore, we hypothesize that El Niño-like conditions over long timescales (or El Padre [Ravelo et al, 2014] conditions) caused the overall thermocline deepening and east to west gradient decrease, which well explains the southward isotopic shift from 27.6 to 27.4 Ma in the eastern equatorial Pacific. On the other hand, Resig [1993] found that biserial planktic foraminifers (high-productivity indicator) are rare or absent from the late Oligocene to early Miocene (~28 to 10 Ma) and suggested depressed thermocline during the interval at Site 807 in the western equatorial Pacific. Concomitant thermocline deepening in the eastern and western equatorial Pacific is consistent with the findings of Ford et al [2015] which proposed a basin-wide thermocline deepening during the Pliocene El Padre.…”
Section: 1002/2016pa002950mentioning
confidence: 99%
“…Amphistegina gibbosa became extinct in the northern Gulf and Salton Trough region at approximately 5.3 Ma (Ingle, 1974;McDougall et al, 1999;Dorsey et al, 2007Dorsey et al, , 2011. The first occurrence of T. anfracta is 5.8 Ma, the range of S. globigerus in the equatorial Pacific is 5.45 to 3.6 Ma, and the range of G. multiloba is Miocene to Pliocene (Blow, 1979;Resig, 1989Resig, , 1993Miranda-Martínez et al, 2017;A.Y.Miranda-Martínez, personal communication, 2017). The highest occurrence of S. globigerus in this section is slightly below the highest occurrence of Globoturborotalita decoraperta, which has a LOD in the western equatorial Pacific at 2.2 Ma (Chaisson and Leckie, 1993).…”
Section: Micropaleontology and Biostratigraphymentioning
confidence: 99%
“…Globorotalia lenguaensis suggests an age no younger than 6.0 Ma, the time when this species became extinct in the Equatorial Pacific Ocean (Wade et al, 2011). The last occurrence datum (LOD) of Streptochilus latus (range: 8.1 to 5.3Ma in the Equatorial Pacific Ocean; Resig, 1989Resig, , 1993 and S. mcdougallae (local range: 6.0 to 5.3 Ma in the Gulf of California; Miranda-Martínez et al, 2017) occurs in the basal part of the green claystone and therefore indicates an age no younger than 5.3 Ma. Detrital sanidine from the DCL in Hart Mine Wash, stratigraphically below the LODs of planktic foraminifers listed above, yielded one 40Ar-39Ar age of 5.0 ± 0.4 Ma (Crow et al, 2016;pers.…”
Section: Cibola Areamentioning
confidence: 99%